Contestation on Political Space Between Islamism and Islamic Group in Presidential Election 2019 - Ali Akhbar Abaib Mas Rabbani Lubis (IAIN Ponorogo, 2020)
Abstract: This paper explains the struggle for political space between Islamism and Islamic groups in the 2019 Presidential Election. The origin of the struggle for political space is closely related to the early history of Indonesian independence. The author considers that historical events are something important to analyze the 2019 Presidential Election issues. This study is a qualitative study using library data through descriptive analysis. The data analysis phase includes data reduction, data presentation, and drawing conclusions. The author uses the triadic concept approach to spatial practise, representations of space, and representational spaces as a theoretical framework for analysis. The discussion of this article results in the conclusion that the “failure of political Islam” in the 2019 Presidential Election cannot be enforced. The 2019 presidential election showed that the struggle for political space was dominated by the Islamism group supporting Prabowo-Sandi and the Islamic group supporting Jokowi-Ma'ruf. Other explanations reveal that the debate and struggle over the political space of the Indonesian State is the impact of the historical cycle of independence. In the context of democracy, the political struggle over space is permissible, but every dynamic of the struggle over political space must be constitutional.الملخص: ستشرح هذه المقالة النضال من أجل الفضاء السياسي بين الإسلامية والجماعات الإسلامية في الانتخابات الرئاسية لعام 2019. يرتبط أصل النضال من أجل الفضاء السياسي ارتباطًا وثيقًا بالتاريخ المبكر لاستقلال إندونيسيا. يرى المؤلف أن الأحداث التاريخية هي شيء مهم لتحليل قضايا الانتخابات الرئاسية لعام 2019. هذه الورقة عبارة عن دراسة نوعية باستخدام بيانات المكتبة من خلال التحليل الوصفي. تتضمن مرحلة تحليل البيانات تقليل البيانات وعرض البيانات واستخلاص النتائج. يستخدم المؤلف نهج المفهوم الثلاثي للممارسة المكانية ، وتمثيل الفضاء ، والمساحات التمثيلية كإطار نظري للتحليل. تؤدي مناقشة هذه المقالة إلى نتيجة مفادها أنه لا يمكن تنفيذ